Model-based evaluation of decentralised electricity markets at different phases of the German energy transition - David Ritter; Christoph Heinemann; Dierk Bauknecht; Christian Winger; Franziska Flachsbarth (ZBW - Leibniz Information Centre for Economics, 2021)
This paper investigates decentralised markets in the German electricity system, defined as markets in specific regions in which regional electricity demand is met primarily by regional generation and the remaining demand is met on a system-wide level in a second step. The research question is: What impact do the size of decentralised markets and the type of authorised participants have in different levels of the energy transition? The results show that the greatest effects from decentralised markets are caused by an increased usage of gas-fired power plants, as they are the major dispatchable generators in the future electricity system, resulting in significantly higher CO2 emissions and electricity generation costs, but also higher local self-supply rates. With very high RES-E shares the results hardly differ between the reference case and decentralised market models. The size of decentralised markets has a lower impact than limited access for certain fuel types or generation capacity size. Although decentralised markets can reduce the load on the grid, the need for grid expansion does not decrease. Overall, we conclude that from a system perspective decentralised markets can lead to negative effects if they are not regulated appropriately, especially during the transformation phase of the electricity system.
Keywords: C61; D47; O21; 330; decentralised markets; local energy markets; electricity market modelling; renewable integration; energy transition